Anti-oxidant and anti-acetylcholinesterase activities of Zygophyllum album (Bangladesh Journal of Pharmacology, 2015)
The present study was carried out to explore the anti-acetylcholinesterase activity and anti-oxidant effect as well as content of phenolic compounds of various extracts from Zygophyllum album. It was observed that dichloromethane and ethanol extracts were endowed with a powerful anti-acetylcholinesterase activity with IC50 values of 40 and 58 µg/mL, respectively. These two extracts exhibited the highest DPPH radical scavenging activity (IC50=0.2 mg/mL), the highest total anti-oxidant capacity (185.2 and 222.4 mg vitamin E/mg extract, respectively), the highest reducing power effect, and the highest ?-carotene bleaching capacity. The findings showed that the extents of anti-acetylcholinesterase activity of Z. album extracts as well as their anti-oxidant capacity are in accordance with their phenolic contents. Hence, Z. album leaves would be useful against Alzheimer's disease.Video Clip of Methodology:Determination of flavonoids content:  2 min 50 sec   Full Screen   Alternate